Differentiation of water-related traits in terrestrial and epiphytic Cymbidium species - Zhang, Shi-Bao; Dai, Yan; Hao, Guang-You; Li, Jia-Wei; Fu, Xue-Wei; Zhang, Jiao-Lin (Frontiers in Plant Science, 2015)
Epiphytes that grow in the canopies of tropical and subtropical forests experience different water regimes when compared with terrestrial plants. However, the differences in adaptive strategies between epiphytic and terrestrial plants with respect to plant water relations remain poorly understood. To understand how water-related traits contrast between epiphytic and terrestrial growth forms within the Cymbidium (Orchidaceae), we assessed leaf anatomy, hydraulics, and physiology of seven terrestrial and 13 epiphytic species using a common garden experiment. Compared with terrestrial species, epiphytic species had higher values for leaf mass per unit area (LMA), leaf thickness (LT), epidermal thickness, saturated water content (SWC) and the time required to dry saturated leaves to 70% relative water content (T70). However, vein density (Dvein), stomatal density (SD), and photosynthetic capacity (Amax) did not differ significantly between the two forms. T70 was positively correlated with LT, LMA, and SWC, and negatively correlated with stomatal index (SI). Amax showed positive correlations with SD and SI, but not with Dvein. Vein density was marginally correlated with SD, and significantly correlated with SI. Overall, epiphytic orchids exhibited substantial ecophysiological differentiations from terrestrial species, with the former type showing trait values indicative of greater drought tolerance and increased water storage capacity. The ability to retain water in the leaves plays a key role in maintaining a water balance in those epiphytes. Therefore, the process of transpiration depends less upon the current substrate water supply and enables epiphytic Cymbidium species to adapt more easily to canopy habitats.